Social Security Issues in Developing Countries : The Latin American Experience. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The paper surveys the major economic, financial, and administrative issues that confront social security systems in Latin America. The larger systems have contributed substantially to public sector financial disequilibria. Expenditures of the younger systems with more limited coverage could increase dramatically as the pension plan matures, life expectancy increases, and coverage is broadened, but the narrow revenue base will force a tradeoff between broader coverage and the generosity of benefits. Most plans are pay-as-you-go, and the case for full or partial funding is not found to be compelling. The inflationary environment can have a substantial effect on the financial balance, even under full indexation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet